ANALISIS DEBIT PUNCAK SUNGAI AIR TETAP KABUPATEN KAUR DENGAN PENDEKATAN METODE HIDROGRAF SATUAN SINTESIK (HSS) - Martin, Roy; Fauzi, Muhammad; Amri, Khairul (Inersia: Jurnal Teknik Sipil, 2020)
The  Tetap Watershed covers an area of 12967 hectares (Ha) and is located in Kaur Regency, Bengkulu Province. The purpose of this study was to obtain peak discharge due to the intensity of rainfall in the Fixed Watershed using the HSS Gama 1, HSS Nakayasu and HSS Snyder methods. Estimated amount of peak discharge is input material for water building planning. Hydrological analysis to obtain peak discharge in this way uses daily rainfall data for 10 years. Based on the calculation of the frequency distribution of the 3 rainfall methods, namely the Gumbel Type I distribution method, Pearson Log Type III, and Normal Log, the method used for the calculation of the planned rainfall is the Gumbel Type I Method with return periods 2, 5, 10, 25, 50 and 100 years, that is 87,566 mm; 114,867 mm; 132,940 mm; 155,782 mm; 172,785 mm and 189,543 mm. From the results of the hydrological analysis, the peak discharge in the Fixed Watershed using the HSS Gama 1 Method for return periods 2, 5, 10, 25, 50, and 100 years is 95.93 mm; 117.40 mm; 136.41 mm; 156.23 mm; 170.81 mm and 185.36. Nakayasu HSS method for return periods of 2, 5, 10, 25, 50, and 100 years in the amount of 90.65 mm; 126.21 mm; 142.92 mm; 160.76 mm; 185.05 mm and 202.45. Snyder HSS method for return periods of 2, 5, 10, 25, 50, and 100 years that is equal to 81.79 mm; 94.71 mm; 110.17 mm; 122.33 mm; 133.60 mm and 144.85. The Nakayassu HSS method, which is 202.45 m3 / second with a peak time of 2.57 hours, is the largest and for the Snyder HSS results the smallest of the two other methods, namely 144.85 m3 / second with a peak time of 5.732 hours.